Catheter ablation of papillary muscle arrhythmias: Implications of mitral valve prolapse and systolic dysfunction. Issue 7 (28th May 2018) - Lee, Adam; Hamilton‐Craig, Christian; Denman, Russell; Haqqani, Haris M.
Abstract: Background: The left ventricular (LV) papillary muscles are important components of the mitral valve apparatus. Catheter ablation of ventricular arrhythmias from these sites is challenging. We aim to describe the association between LV papillary muscle ventricular arrhythmias (VAs) and mitral valve prolapse (MVP), and to determine the outcomes of ablation in these patients with a focus on those with MVP and cardiomyopathy. Methods: A total of 152 patients underwent 170 consecutive procedures for ablation of focal VAs. MVP and cardiomyopathy were diagnosed by echocardiography. Outcomes following ablation were assessed in three groups: (1) LV papillary muscle VAs versus other sites, (2) LV papillary muscle VAs by the presence of MVP, and (3) LV papillary muscle VAs in the setting of cardiomyopathy. Results: Nine of 23 (39%) patients undergoing ablation of LV papillary muscle VAs had MVP compared to none of 129 (0%) patients at other sites (P < 0.001). In the former group, acute procedural success was achieved in 60% and 80% of those with and without MVP, respectively (P = 0.28). Medium‐term outcomes were comparable (P = 0.75). In patients with cardiomyopathy, the median LV ejection fraction improved from 40% to 54% following ablation (P = 0.007). Conclusions: Although MVP is strongly associated with LV papillary muscle VAs, MVP does not adversely affect the acute or medium‐term outcomes of ablation. Systolic function can improve following ablation in patients with ectopy‐mediated cardiomyopathy due to papillary muscle VAs.